Socioeconomics of Urban Agriculture in Curuçambá Neighborhood, Metropolitan Region of Belém, Brazilian Amazon - Júnior, Paulo Silvano Magno Fróes; Rebello, Fabrício Khoury; Martins, Cyntia Meireles; Lopes, Maria Lúcia Bahia; Souza, Caio Cezar Ferreira de; Saraiva, Joyce dos Santos; Loureiro, João Paulo Borges de; Barbosa, Antônia do Socorro Aleixo; Martins, Geany Cleide Carvalho; Araújo, Janayna Galvão de; et al. (Journal of Agricultural Studies, 2022)
This study aims to characterize the agricultural production systems under urban and peri-urban agriculture (UPA) in the Curuçambá neighborhood; identify the main techniques and technologies adopted, cultivations and creations conducted, and the activity relationship within the Metropolitan Region of Belém (RMB); and estimate the production contribution to family consumption complementarily and exploratorily. Data were obtained through interviews conducted among 63 residents in the neighborhood (representing 52.50% of the universe) by monitoring the food consumption of six producers’ families for two weeks and georeferencing images from Google Satellite. Farmers were mainly from the northeast of Pará (57.14%) and other Brazilian states such as Maranhão (9.52%), Ceará (9.52%), and Paraíba (1.59%). Clearly, urban agriculture in the region was established during the migration of rural areas to Amazonian cities. Generally, most farmers had reached elementary school II (69.84%) and had an average monthly income of one to two minimum wages (50.79%). Agricultural production was promoted by approximately 111 residences in the neighborhood and was based on horticulture and small livestock keeping. Additionally, the items analyzed were allegedly produced in six production systems: common beds (71.43%), suspended beds (12.70%), fruticulture (6.35%), agroforestry yards (3.17%), hydroponics (4.76%), and aquaponics (1.59%), and were directed to supply the RMB markets. On average, 30.89% of farmers’ income covered family consumption; we estimated the opportunity cost of consumption for the five main products cultivated in the neighborhood (jambu, lettuce, coriander, chicory, and cariru) as R 79.88 monthly, accounting for 8.37% of the current minimum wage at that time.